PENGARUH PENGGUNAAN BERBAGAI JENIS LITTER TERHADAP BOBOT HIDUP, BOBOT KARKAS, DAN BOBOT LEMAK ABDOMINAL BROILER FASE FINISHER DI OPEN HOUSE - Yaner selim nubatonis; Farida kusuma astuti; Sumarno sumarno; Nonok supartini (Maduranch : Jurnal Ilmu Peternakan, 2023)
This study aimet to decide the impact of utilizing different sorts of litter on live weight, body weight and stomach fat of finisher work grill chickens in an open house. This examination was led for 24 days from 01 Walk to 24 Walk 2022 in Gading Kulon Town, Dau Area, Malang Rule. The material utilized in this study were 27 DOC unsex oven chickens CP 707 strain, as well as starter and finisher stage grill proportions. The litter materials utilized incorporate rice husks, wood sawdust, and rice straw. This study utilized a totally randomized plan with 3 medicines and 3 replications, and every replication comprised of 3 chickens. The treatment applied was P1 (Rice Husk); P2 (wood sawdust); P3 (rice straw). Live weight, corpse and stomach fat were estimated in the finisher stage (35 days old). The information acquired were dissected by examination of difference (ANOVA). In view of the consequences of the review, it was reasoned that the utilization of wood sawdust litter (P2) goodly affected live weight and corpse weight of finisher stage ovens raised in an open house when contrasted with rice husk (P1) and rice straw (P3), albeit the aftereffects of the review were not fundamentally unique. , the utilization of rice husk litter, wood sawdust, and rice straw didn't influence the stomach fat load of finisher work ovens in open houses.Keywords: Litter, Fisiologi Broiler, Open House